2013
DOI: 10.1021/pr4003678
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification of Unique Photoreceptor Disc Components Reveals the Presence of PRCD, a Protein Linked to Retinal Degeneration

Abstract: Visual signal transduction takes place on the surface of flat membrane vesicles called photoreceptor discs, which reside inside the light-sensitive outer segment organelle of vertebrate photoreceptor cells. While biochemical studies have indicated that discs are built with a handful of highly specialized proteins, proteomic studies have yielded databases consisting of hundreds of entries. We addressed this controversy by employing protein correlation profiling which allows identification of unique components o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 49 publications
2
75
0
Order By: Relevance
“…Association of PRCD with Membranes Is Not Dependent on Palmitoylation-A previous study revealed that PRCD is one of 11 proteins exclusively present in the photoreceptor disc membrane (16). We wanted to investigate the contribution of protein palmitoylation in the membrane association of PRCD.…”
Section: Prcd Is a Palmitoylated Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Association of PRCD with Membranes Is Not Dependent on Palmitoylation-A previous study revealed that PRCD is one of 11 proteins exclusively present in the photoreceptor disc membrane (16). We wanted to investigate the contribution of protein palmitoylation in the membrane association of PRCD.…”
Section: Prcd Is a Palmitoylated Proteinmentioning
confidence: 99%
“…A proteomic study demonstrated that PRCD is one of 11 proteins exclusively present in the photoreceptor outer segment (OS) disc membrane (16). The presence of PRCD within the OS disc membranes suggests that it plays an important role in photoreceptor function and/or maintenance.…”
mentioning
confidence: 99%
“…The mass spectrometry analysis performed on samples immunoprecipitated with the CNGA1 and CNGB1 antibodies failed to detect ankyrin G peptides. In fact, ankyrin G has not been found in massspectrometric-based proteomic studies of photoreceptor outer segments (Kiel et al, 2011;Kwok et al, 2008;Reidel et al, 2011;Skiba et al, 2013). Considering the size of this protein it is surprising that these proteomics studies have failed to detect peptides from ankyrin G in outer segment preparations.…”
Section: Comparison Of 41g and Cngs Distribution In Photoreceptorsmentioning
confidence: 99%
“…Mouse rod outer segments (OS) are in effect genetically manipulable, femtoliter test tubes whose protein constituents (15,16), as well as their biochemical reactions (17)(18)(19) and light-stimulated translocations (20)(21)(22), are well known and have been measured primarily with ex vivo methods. Advances in imaging technology have now made it possible to achieve subcellular-resolution imaging of the mouse retina in vivo (23)(24)(25)(26).…”
mentioning
confidence: 99%